STRATEGI PENGELOLAAN DANA BEASISWA KIP KULIAH GUNA MENGATASI PERILAKU KONSUMTIF DAN MENINGKATKAN PRESTASI AKADEMIK DI FAKULTAS EKONOMI UNIVESITAS NAHDLATUL ULAMA SIDOARJO - Gunawan, Zulfaa; Fahriani, Dian (JURNAL AKUNTANSI BARELANG, 2025)
This study aims to analyze the strategy of managing KIP Lecture scholarship funds to overcome consumptive behavior and improve the academic achievement of students of the Faculty of Economics, Nahdlatul Ulama University of Sidoarjo. The research method used is qualitative with a descriptive approach. Data were obtained through interviews with scholarship recipient students and the Head of Student Welfare. The results showed that although the scholarship aims to support education, some students tend to allocate funds for consumptive needs. The university implemented various strategies such as financial reporting mechanisms, financial literacy education, and the provision of student cooperatives as a means of saving. However, challenges such as late reporting and lack of financial awareness are still faced. Therefore, stricter supervision and increased student awareness in financial management are needed. With the right strategy, it is hoped that students can be more optimal in utilizing the scholarship to improve their academic performance